Heparin mimetics - Coombe, Deidre; Kett, W. (2012)
Explorations of the therapeutic potential of heparin mimetics, anionic compounds that are analogues of glycosaminoglycans (GAGs), have gone hand-in-hand with the emergence of understanding as to the role of GAGs in many essential biological processes. A myriad of structurally different heparin mimetics have been prepared and examined in many diverse applications. They range in complexity from heterogeneous polysaccharides that have been chemically sulphated to well-defined compounds, designed in part to mimic the natural ligand, but with binding specificity and potency increased by conjugation to non-carbohydrate pharmacophores. The maturity of the field is illustrated by the seven heparin mimetics that have achieved marketing approval and there are several more in late-stage clinical development. An overview of the structural determinants of heparin mimetics is presented together with an indication of their activities. The challenges in developing heparin mimetics as drugs, specificity and potential toxicity issues, are highlighted. Finally, the development path of three structurally very different mimetics, PI-88 ®, GMI-1070 and RGTAs, each of which is in clinical trials, is described. © 2012 Springer-Verlag Berlin Heidelberg.